Spontaneous Cutaneous Hepatic Hydatid Transit - Salgado Moreira, Moisés; Ramos, Juan M (Cirugía del Uruguay, 1980)
A patient suffered from a rare case of hydatic migration far many months befare diagnosis was finally established. The paper contains a review of causes which favour or affect hydatid migration outwards from liver. Finally the author revises the conduct followed, which cures hydatidosis and prevents operatory and immediate postoperatory complications, as well as recurrences and sequela to the disease.